THE DETERMINING THE AVAILABLE TIME FUND FOR USING THE AIRSPACE OF DIFFERENT CLIMATIC ZONES BY HELICOPTER ROBINSON R-44 TAKING INTO ACCOUNT ITS OPERATING RESTRICTIONS - P. M. Polyakov (Naučnyj Vestnik MGTU GA, 2016)
The article touched upon the problem of justifying the use of the helicopter Robinson R-44 when working in different climatic zones. The operating constraints of the helicopter R-44 are suggested as the main criterion limiting the time fund.